The influence of teachers' teaching strategies and students' learning environment on civic learning motivation - Noviyandika Nurul Saputri; Wibowo Heru Prasetiyo; Sri Gunarsi (Universitas Tanjungpura, 2023)
This article examines the effect of teacher-teaching strategies and student learning environments on Civic learning motivation. This study used a correlational design with a quantitative approach. Data was collected using a questionnaire and then analyzed using SPSS 26 For Windows with multiple linear regression analysis techniques. The results showed that the significance value was 0.000<0.05 with the Fcount value greater than Ftable, namely 27.534>3.07. These findings show that the hypothesis is accepted, meaning that the teacher's teaching strategy and environment positively and significantly affect the motivation to learn Civic. This amount is 31.6%. Thus, teachers must optimize teaching strategies and a conducive learning environment to foster motivation to learn Civic. This research can become the basis for further research to improve Civic learning outcomes in schools.